POLA INTERAKSI SERANGGA-GULMA PADA EKOSISTEM SAWAH SURJAN DAN LEMBARAN DALAM MENDUKUNG PENGENDALIAN HAYATI - , TIEN AMINATUN, S,.SI.,M.SI. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Weeds, which interact with insects, have positive role in biological control. However, we need to investigate the pattern of insect-weed interaction which support biological control. Agriculture practice affects the quantity and types of the interactions. Habitat modification and application of insecticide in agricultural ecosystems affect the food web structure. The pattern of the interaction can be shown by food web analysis. The aims of this research were